2016
DOI: 10.21037/jtd.2016.08.73
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of patients with small cell lung cancer without prophylactic cranial irradiation

Abstract: Background: Prophylactic cranial irradiation (PCI) is indicated for limited disease (LD) in small cell lung cancer (SCLC) patients who achieve a complete or near-complete response; however, it is sometimes not administered because of possible adverse reactions or patient refusal. Here we assessed treatment outcomes among patients with SCLC who were not treated with PCI. Conclusions:The results of our study demonstrated that the outcomes of treatment without PCI were improved, as compared with those of previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…There is little published information available on the survival outcomes and prognostic factors of patients who decline PCI, in the recent clinical situations in which PCI is accepted as a standard treatment for LS-SCLC. A retrospective study that reported treatment outcomes of 60 LS-SCLC patients who did not receive PCI after a CR or near-CR showed that brain metastasis, performance status, and T-stage were significantly related to OS [13]. Another recent study that performed a multivariate analysis with 153 patients reported that high T-stage, high neutrophil-to-lymphocyte ratio, early thoracic radiotherapy, and fewer chemotherapy cycles were risk factors for brain metastasis [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little published information available on the survival outcomes and prognostic factors of patients who decline PCI, in the recent clinical situations in which PCI is accepted as a standard treatment for LS-SCLC. A retrospective study that reported treatment outcomes of 60 LS-SCLC patients who did not receive PCI after a CR or near-CR showed that brain metastasis, performance status, and T-stage were significantly related to OS [13]. Another recent study that performed a multivariate analysis with 153 patients reported that high T-stage, high neutrophil-to-lymphocyte ratio, early thoracic radiotherapy, and fewer chemotherapy cycles were risk factors for brain metastasis [12].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only a few reports on the treatment outcomes of patients who did not receive PCI have been published according to current medical treatments [12,13]. An understanding of the treatment outcomes and prognostic factors may be helpful in deciding whether or not to apply PCI to patients with comorbidity, despite a good response to initial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the rate of patients received PCI were relatively low. Although a recent study from Japan showed PCI played a detrimental role in the outcome of patients with LS-SCLC, 28 PCI is generally considered as a component of the treatment of patients with LS-SCLC. PFS and OS might be impaired by low PCI rate.…”
Section: Discussionmentioning
confidence: 99%
“…This was because the current standard of care in patients with LD-SCLC who have a good response to initial chemoradiotherapy is to receive PCI, although no individual randomized trial with PCI has demonstrated a significant OS prolongation for patients with LD-SCLC. Only few reports on patients with LD-SCLC who received standard chemoradiotherapy without PCI are available [ 35 37 ]. However, no studies about the clinical benefits of PCI in patients with LD-SCLC confirmed with no BM on MRI have been conducted.…”
Section: Discussionmentioning
confidence: 99%